The Federal Role in Terrorism Insurance Evaluating Alternatives in an Uncertain World - Dixon, Lloyd (RAND Corporation, 2007)
What are the Terrorism Risk Insurance Act's effects on the market for terrorism insurance? What would be the effect of enhancing provisions for nuclear, biological, chemical, and radiological (NBCR) attacks? The authors conclude that the program yields positive outcomes in a number of dimensions for conventional attacks and identify specific reforms that can improve results for NBCR attacks.